Nurse Practitioner Practice Environments in Primary Care and Quality of Care for Chronic Diseases. Issue 9 (September 2018) - Poghosyan, Lusine; Norful, Allison A.; Liu, Jianfang; Friedberg, Mark W.
Abstract : Background: The chronic disease burden in the United States represents a significant challenge for the primary care system. The nurse practitioner (NP) workforce can help meet the demand for care; however, organizational barriers such as poor practice environments prevent NPs from delivering high quality care. Objectives: We investigated the relationship between NP practice environments and quality of care for chronic diseases. Research Design: We fit regression models to assess cross-sectional associations between claims-based quality measure performance and survey data on NP practice environments in Massachusetts. Subjects: We used survey data from 221 primary care NPs from 118 practices. We obtained quality of care data for patients with asthma, diabetes, and cardiovascular disease. Measures: The Nurse Practitioner Primary Care Organizational Climate Questionnaire was used to measure practice environments with its following 4 subscales: NP-Physician Relations, Independent Practice and Support, Professional Visibility, and NP-Administration Relations. Three Healthcare Effectiveness Data and Information Set measures were used to evaluate the quality of care. Results: A 1-SD increase in the organizational-level NP-Administration Relations subscale score was associated with a near doubling of the odds of receiving medication management for asthma. A 1-SD increase in the organizational-level Independent Practice and Support subscale score was associated with a 60% increase in the odds of receiving recommended screening for cardiovascular disease. There was no impact on diabetes care measure. Conclusions: NP practice environment affected the quality of care for 2 chronic conditions. Efforts should be implemented to improve NP practice environment to potentially improve care quality.